Leading strategies and research advances for the restoration of graphite from expired Li+ energy storage devices. Issue 6 (December 2021) - Perumal, P.; Andersen, Shuang Ma; Nikoloski, Aleksander; Basu, Suddhasatwa; Mohapatra, Mamata
Abstract: Due to prominent interest, enlarged use of several portable appliances and electric vehicles, lithium-ion batteries (LIBs) are extremely desired as a core power source. Till now, graphite is recognized as a negative electrode material in utmost commercial LIBs. Expanding the usage of graphite sources may cause the deficiency in supply and to be included in the directory of most critical material in future. Therefore, recycling of graphite from spent LIBs is a healthy option to prevent the challenges in the supply and demand. Also, recycling technology is a most promising plan and resource-saving route for the future along with economic as well as environmental potential benefits. Nonetheless, reclamation of graphite from spent LIBs emerged to be missing and rare in the literature. Therefore, this review has been planned to initiate the recycling strategy of the graphite carbon from spent devices, and importance of graphite recycling is discussed in detail. Notably, this review provides an overview on revivification of graphite with use of existing metallurgical routes and novel facile experimental techniques. Also, strong focuses on the transformation of spent graphite into graphene oxides/functional composites with rich electrochemical performance. The role of graphene oxide other than the energy storage field is viewed and analyzed in this review. Noteworthy, challenges in the recycling process and its future perspective also deeply discussed here. Graphical Abstract: ga1 Highlights: Current status and impact of anode recycling from expired LIBs are overviewed in a detailed manner. Electrochemical performances of remade graphite with use of various metallurgical processes/novel routes are compared. Besides, critical analyses are addressed for the conversion of graphite into higher valuable graphene products.